Investigating industrial by-product for soil conditioning addressing environmental risk and waste reduction alternatives - Eli SyafiqahAziman; Aznan Fazli Ismail; Siti Fatimah Jubri; Amalina Abd Rahman; Khairiah Rosli; Wan Mohd Razi Idris; Sahibin Abd Rahim (Springer Nature, 2025)
Condisoil is an innovative soil conditioner formulated from industrial by-products specifically Water Leach Purification and Neutralisation Underflow residues derived from rare-earth processing. This study investigates its potential to improve sandy soils for paddy cultivation, a vital sector for Malaysia’s food security. Unlike conventional soil amendments, Condisoil promotes sustainability by repurposing industrial by-products and addressing disposal challenges. However, due to its origin, assessing elemental distribution and soil-to-rice grain transfer factors is essential to ensure its agricultural safety. Activity concentrations of naturally occurring radionuclides (NORM) 226Ra, 228Ra, and 40K in Condisoiltreated soils ranged from 66.5 to 143.1, 49.7 to 70.6, and 391.6 to 432.2 Bq/kg, respectively, over two paddy planting seasons. In rice grains, NORM levels were significantly lower, ranging from 0.93 to 9.20 (226Ra), 0.03 to 0.53 (228Ra), and 89.14 to 147.95 (40K) Bq/kg. Heavy metal As, Sb, Cr, Cd, and Pb concentrations in soils remained below Malaysian safety standards, while rice grains contained in the range of 0.2–1.4, 0.7–3.0, 0.1–0.1, and 0.5–1.8 mg/kg, respectively. TF values for radionuclides and heavy metals ranged from 0.00 to 0.00–0.30 and 0.01–1.0, respectively. The estimated annual effective dose from rice consumption remained below the 1.0 mSv/year safety threshold. While the uptake of most elements was minimal, lead (Pb) and antimony (Sb) exhibited HI values >1, and the TF value of cadmium (Cd) was >1, indicating potential health risks. Therefore, environmental monitoring is essential before large-scale application. This study highlights Condisoil’s potential in sustainable agriculture and waste valorization, though strict heavy metal monitoring protocols are necessary to ensure long-term food safety when using industrial by-products as soil conditioners.